2014
DOI: 10.1097/hjh.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in prevalence of femoral but not carotid atherosclerosis

Abstract: In the present study, atherosclerotic lesions are more prevalent at the right than at the left femoral artery. This finding highlights the possible role of local arterial geometry in the development of atherosclerosis and underscores the importance of the choice of body side when assessing vascular health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…36 This hypothesis is even supported by differences between the distribution of atherosclerotic plaques in carotid and femoral sites already highlighted by previous authors. For example, Bossuyt et al observed a significant right-left difference in IMT of CFA but not of CCA and suggested a possible role of local geometry in the development of atherosclerosis 37 ; however, this side difference has not been observed in our series. This idea is also strengthened by pathology and biochemical studies: Pathology studies demonstrated that atherosclerotic plaques sited in different segments of the arterial tree have commonalities in cell types, but their relative numbers and amount of connective tissue and lipids can vary considerably 36 ; biochemical studies proved a different correlation between circulating lipoprotein and femoral plaques in comparison with carotid plaques.…”
Section: Discussioncontrasting
confidence: 79%
“…36 This hypothesis is even supported by differences between the distribution of atherosclerotic plaques in carotid and femoral sites already highlighted by previous authors. For example, Bossuyt et al observed a significant right-left difference in IMT of CFA but not of CCA and suggested a possible role of local geometry in the development of atherosclerosis 37 ; however, this side difference has not been observed in our series. This idea is also strengthened by pathology and biochemical studies: Pathology studies demonstrated that atherosclerotic plaques sited in different segments of the arterial tree have commonalities in cell types, but their relative numbers and amount of connective tissue and lipids can vary considerably 36 ; biochemical studies proved a different correlation between circulating lipoprotein and femoral plaques in comparison with carotid plaques.…”
Section: Discussioncontrasting
confidence: 79%
“…On the other hand, at the femoral bifurcation, asymmetry of atheromatous plaques is observed [9]. These clinical facts can be explained by the almost rectilinear path of the carotid artery, whereas the common femoral artery and its branches show a tortuous path [9]. Indeed, our work shows, through a statistical correlation, that the tortuosity of the common femoral artery has an influence on its atheromatous calcification.…”
Section: Discussionmentioning
confidence: 50%
“…A comparative study on the symmetry between the carotid artery and the femoral bifurcation, concerning the deposition of atheromatous plaques, shows perfect symmetry at the carotid level. On the other hand, at the femoral bifurcation, asymmetry of atheromatous plaques is observed [9]. These clinical facts can be explained by the almost rectilinear path of the carotid artery, whereas the common femoral artery and its branches show a tortuous path [9].…”
Section: Discussionmentioning
confidence: 99%
“…These results seem to suggest that genetic factors, rather than other factors shared by twins (such as constitutional or local factors, e.g. vessels' angulation) [29], are involved in the occurrence of atherosclerotic plaques and probably in the atherogenic process itself. However, it cannot be excluded that specific genetic or environmental risk factors could affect different vascular territories.…”
Section: Discussionmentioning
confidence: 87%